1989
DOI: 10.1007/bf01187084
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric studies on the microvasculature of pre- and paravertebral sympathetic ganglia in the adult and aged rat by light and electron microscopy

Abstract: Morphometric measurements have been made by light and electron microscopy on sections of perfused sympathetic ganglia from rats of 6-24 months of age with special reference to the microvascular bed. Capillaries, postcapillary venules and small venules comprised the majority of the vessels studied but small arterioles were, in addition, included in the light microscopical part of the study. Light microscopical measurements using image analysis showed that there was a decrease in the density of the microvascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

1993
1993
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
1
10
0
1
Order By: Relevance
“…There was an obvious decrease in this percentage with ageing. These results are similar to the decrease in the density of the microvascular bed and in the total vascular luminal area observed in the pre-and paravertebral sympathetic ganglia in aged Wistar rats (Baker et al, 1989). Also, this is in agreement with observations on normal sural nerves in man (Giannini and Dyck, 1993) and this decrease might be a normal feature of ageing nerves.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…There was an obvious decrease in this percentage with ageing. These results are similar to the decrease in the density of the microvascular bed and in the total vascular luminal area observed in the pre-and paravertebral sympathetic ganglia in aged Wistar rats (Baker et al, 1989). Also, this is in agreement with observations on normal sural nerves in man (Giannini and Dyck, 1993) and this decrease might be a normal feature of ageing nerves.…”
Section: Discussionsupporting
confidence: 91%
“…The intraneural vascular pattern is subject to a wide range of variation from level to level and subject to subject and there is no pattern which is constant or characteristic for any part of the nerve (Sunderland, 1978). Quantitative approaches to the study of the microvasculature in the peripheral nervous system have been rarely described (Baker et al, 1989) and, despite some studies involving somatic nerves (Macarian and Smith, 1968;Bell and Weddell, 1984b) and autonomic ganglia (Baker et al, 1989;, information on autonomic nerves are scanty. Also, the literature provides information on number , permeability (Wadhwani et al, 1991) and ultrastructure (Bell and Weddell, 1984b; of the peripheral nerves vessels, with no information on the relation between nerve fascicles size and age, as on the blood vessels behavior with this relation.…”
Section: Introductionmentioning
confidence: 99%
“…and prevertebral ganglia of other animals was the appearance of its intraganglionic blood vessels. Fenestrated blood vessels, commonly found in prevertebral ganglia of rat and guinea pig (Al-Khafaji et al, 1980;McDonald and Blewett, 1981;Baker et al, 1989) were not found in the mouse S.m.g. All blood vessels examined in the mouse S.m.g.…”
Section: Discussionmentioning
confidence: 97%
“…Many capillary beds have similarly been shown to maintain a source of VEGF even into adulthood (29). The persistence of VEGF expression in the DRG suggests that VEGF may serve functions other than direct support of vascular integrity in the adult DRG: one possible role is the maintenance of capillary network fenestrae, as have been shown to exist in other paravertebral ganglia (41).…”
Section: Discussionmentioning
confidence: 99%